A father with postpartum psychosis. (8th May 2012) - Shahani, Lokesh
Abstract : Postpartum psychosis is a rare, however severe mood disorder in the perinatal period. It is most commonly associated with postpartum bipolar disorder. The author reports a case where a male patient with psychosis was admitted to the psychiatric unit 5 days after his wife gave birth to their male child. The patient was very concerned about the well being of his child and was afraid that something bad would happen to his child. The patient was diagnosed with an acute manic episode with psychotic symptoms and treated with olanzapine and lithium. The patient has been continued on therapeutic dose of lithium without any relapse of the symptoms, 3 months after the initial episode. The role of psychological stress in precipitating such a severe mood or psychotic disorder needs to be highlighted.